Activation and inflammation of the venous endothelium in vein graft disease. (October 2017) - Ward, Alexander O.; Caputo, Massimo; Angelini, Gianni D.; George, Sarah J.; Zakkar, Mustafa
Abstract: The long saphenous vein is the most commonly used conduit in coronary artery bypass graft (CABG) surgery when bypassing multiple diseased arteries; however, its use is complicated by the development of vascular inflammation, intimal hyperplasia and accelerated atherosclerosis leading to compromised graft efficacy. Despite refinement of surgical techniques to improve graft patency, late vein graft failure remains a significant problem. Moreover, there is a lack of pharmacological interventions proven to be effective in the treatment of late vein graft failure. A greater understanding of the molecular nature of the disease and the interactions between endothelial and smooth muscle cells as a result of alterations in local haemodynamics may assist with designing future beneficial pharmacological interventions. Venous endothelial cells (ECs) are physiologically adapted to chronic low shear stress; however, once the graft is implanted into the arterial circulation, they become suddenly exposed to acute high levels of shear stress. A small number of in vitro and ex vivo studies have demonstrated that acute high shear stress is associated with the activation of a pro-inflammatory profile in saphenous vein ECs, which may be mediated by mitogen-activated protein kinase (MAPK) and nuclear factor-κB (NF-κB) signalling pathways. The impact of acute changes in shear stress on venous ECs and the role of ECs in the development of intimal hyperplasia remains incomplete and is the subject of this review. Highlights: Vein grafting remains challenging due to development of intimal hyperplasia (IH) and atherosclerosis. IH is preceded by endothelial cells (EC) activation, which induces initial vascular inflammation. EC activation is mediated by combined actions of NF-κB and MAPK pathways. Suppression of early EC activation may offer therapeutic direction for vein graft failure.